Improving Listening Comprehension of Grade Eleven Students of Senior High School Through Partial Dictation - Anggun Pratiwi; Sudarkam Mertosono; Desrin Lebagi; Nur Sehang Thamrin (Universitas Islam Negeri Palopo, 2025)
The researcher aims to find out whether or not Partial Dictation Technique can improve the listening skill of the eleven grade students’ of SMA Negeri 7 Palu. This research sample was 71 students, divided into 35 students of class XI-2 as the experimental class and 36 students of class XI-4 as the control class. The data were collected through the listening test with listening audio that consisted of the pre-test and post-test. After conducting the treatment, the data indicates that the experimental class showed improvement in their listening skill compared to the control class. The collected data were analyzed using SPSS version 23. The results showed that in the experimental class the mean score of the pre-test was (54.14) and post-test was (77.57). Meanwhile, in the control class the mean score of the pre-test was (47.78) and post-test was (61.39). Based on the results of the t-test sample independence test, the sig (2 tailed) (0.000) value is lower than 0.05. This shows that the alternative hypothesis is accepted. Therefore, the partial dictation technique is effective in developing listening comprehension of grade eleven students of SMAN 7 Palu.